Sustaining Fiction: Preserving Patriarchy in Marvell's Upon Appleton House. - Kadue, Katie (Studies in Philology)
Many readers of Andrew Marvell's Upon Appleton House note the poem's deviation from typical country house poems, finding in this deviation evidence of Marvell's ambivalence, eccentricity, or even, in the poem's challenges to heterosexual norms, "queerness." This essay argues, on the contrary, that Marvell's apparent queerness serves to sustain, rather than threaten, heterosexual norms. Marvell's role is thus analogous to that of the early modern housewife, who, "other" as she was, was integral to the preservation of her household. This parallel between poets and housewives resonates today, as the intellectual labor that preserves culture becomes increasingly devalued and "feminized."